Administration and effects of beta blockers and oxandrolone in severely burned adults: a post hoc analysis of the RE-ENERGIZE trial - Hundeshagen, Gabriel; Blears, Elisabeth; Mertin, Viktoria; Day, Andrew G; Palackic, Alen; Tapking, Christian; Haug, Valentin; Kneser, Ulrich; Bliesener, Björn; Panayi, Adriana C.; Aballay, Ariel; Depret, Francois; et al. (Burns & trauma, 2024)
Prospective randomized trials in severely burned children have shown the positive effects of oxandrolone (OX), beta blockers (BB) and a combination of the two (BBOX) on hypermetabolism, catabolism and hyperinflammation short- and long-term post-burn. Although data on severely burned adults are lacking in comparison, BB, OX and BBOX appear to be commonly employed in this patient population. In this study, we perform a secondary analysis of an international prospective randomized trial dataset to provide descriptive evidence regarding the current utilization patterns and potential treatment effects of OX, BB and BBOX.The RE-ENERGIZE (RandomizEd Trial of ENtERal Glutamine to minimIZE Thermal Injury, NCT00985205) trial included 1200 adult patients with severe burns. We stratified patients according to their receipt of OX, BB, BBOX or none of these drugs (None) during acute hospitalization. Descriptive statistics describe the details of drug therapy and unadjusted analyses identify predisposing factors for drug use per group. Association between OX, BB and BBOX and clinical outcomes such as time to discharge alive and 6-month mortality were modeled using adjusted multivariable Cox regressions.More than half of all patients in the trial received either OX (n = 138), BB (n = 293) or BBOX (n = 282), as opposed to None (n = 487, 40.6%). Per study site and geographical region, use of OX, BB and BBOX was highly variable. Predisposing factors for the use of OX, BB and BBOX included larger total body surface area (TBSA) burned, higher acute physiology and chronic health evaluation (APACHE) II scores on admission and younger patient age. After adjustment for multiple covariates, the use of OX was associated with a longer time to discharge alive [hazard ratio (HR) 0.62, confidence interval (CI) (0.47-0.82) per 100% increase, p = 0.001]. A higher proportion of days on BB was associated with lower in-hospital-mortality (HR: 0.5, CI 0.28-0.87, p = 0.015) and 6-month mortality (HR: 0.44, CI 0.24-0.82, p = 0.01).The use of OX, BB and BBOX is common within the adult burn patient population, with its use varying considerably across sites worldwide. Our findings found mixed associations between outcomes and the use of BB and OX in adult burn patients, with lower acute and 6-month-mortality with BB and longer times to discharge with OX. Further research into these pharmacological modulators of the pathophysiological response to severe burn injury is indicated.
Online veröffentlicht: 21. April 2024
Gesehen am 10.10.2024